Strategi Branding Digital UMKM melalui Konten TikTok (Studi Kasus UMKM Pojok Manis Lamongan) - Kofifa Zunia Lestari; Wulan Zuni Anggraeni Kusuma; Anisatun Fitria; Dinar Gymnastiar Nilasari; Adhelia Dwinanda Riza Saputri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This research aims to explain the digital branding strategy carried out by the Pojok Manis Lamongan MSME through the use of TikTok as a platform for promotion and brand image development. The study uses a qualitative approach with a descriptive case study design. Data were obtained from semi-structured interviews with the business owner, observations of the official TikTok account, and documentation such as digital archives and screenshots of uploaded content. The data were then processed through data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through technique triangulation. The results show that the digital branding strategy mainly focuses on creating visually appealing product promotion videos, maintaining consistent content uploads, and making use of TikTok trends and features, including live streaming, to increase interaction with viewers. The use of TikTok has contributed positively to improving business visibility, increasing the number of customers, and strengthening the brand image of the MSME. However, the planning of the branding strategy is still relatively simple and has not been carried out in a structured manner. As a result, the evaluation of branding success is still limited to the number of views and user engagement levels. Therefore, in order to maximize TikTok as a digital branding medium for MSMEs, more systematic content planning, better digital literacy, and continuous evaluation are needed to support sustainable business growth.